Promotion of freelance services in the digital environment - L. G. Akhmaeva (Цифровая социология)
The article analyses the concept of freelance (temporary, project employment) within the framework of new approaches to employment and changes in the perception of remote and hybrid forms of employment by society and business after the COVID-19 pandemic. The following segments of the labour market where freelancing is the most common element are considered: copywriting, law, software development, design of buildings and structures, creation of graphic, audio and video content, consulting, provision of expertise, tutoring. The portrait of a freelancer is studied in detail according to such characteristics as the region of residence, sex, average age, the share of “real” freelancers and the share of part-timers, experience of interaction with freelance platforms, tax status, single and team players, the reasons for choosing freelancing as a form of employment, the most valuable component of freelancing, the disadvantages of freelancing as a form of employment and motivation of freelancers. The main methods of promoting freelance services in the digital environment are identified: a portfolio site, active maintenance of a professional profile in social networks and its advertising, registration on aggregator sites, freelance and human-cloud platforms. The main element of the portfolio site is highlighted – the works performed by a freelancer (texts, photographs, graphics and similar materials) – along with the key factors that a freelancer needs to consider when creating and maintaining a portfolio site and the most common mistakes